GAMBARAN DETEKSI DINI DEPRESI PADA LANJUT USIA DENGAN PENYAKIT TIDAK MENULAR KRONIS DI KOTA SEMARANG - Kartini Suhas; Ni Made Ayu Wulan Sari; Asti Nuraeni (JURNAL MEDIA KESEHATAN, 2022)
Chronic non-communicable diseases are diseases that often attack the elderly which can cause psychological problems, one of which is depression. This study aims to describe the early detection of depression in the elderly with chronic non-communicable diseases. This research method uses descriptive study analysis techniques. The number of samples in this study were 272 respondents with the sampling technique using cluster sampling and then using random sampling, so that 1 cluster was selected, namely the Kedungmundu Health Center. This research was conducted for 21 days starting from April 09 to April 30. The measuring instrument used is the CESD-R (Center for Epidemiological Studies Depression Scale) questionnaire. Analysis of the data used is univariate analysis with a frequency distribution table. The results of this study found that most of the respondents indicated depression as many as 187 respondents or 68.8%, while those who did not indicated depression were 85 respondents or 31.3%. Based on the results of this study, it is necessary to make efforts to develop health services at the Puskesmas in improving mental service units (Poli Jiwa), to make efforts to prevent mental disorders, especially detection of depression in the elderly with chronic non-communicable diseases by screening at least every 6 months